ABUNDANCES OF N - CAPTURE ELEMENTS IN STARS OF THIN AND THICK DISKS. - Mishenina, T. V.; Gorbaneva, T. I.; Basak, N. Yu.; Soubiran, C.; Kovtyukh, V. V. (Одеські астрономічні публікації, 2007)
Abundances of neutron-capture (n- capture) elements in the stars belonging to thin and thick disks are obtained. The separation of thin and thick stars on kinematic criterion was made early. The spectra were obtained with the ELODIE spectrograph at the 1.93-m telescope of the Observatoire de Haute Provence (France). The determination of elemental abundances was carried out in LTE assumption by model atmosphere method, for Ba and Eu taken into account the hyperfine structure. The dependences of n-capture element abundances on metallicity for thin and thick disks are presented.